THE CLAIM TO UNIQUENESS AND UNIVERSALITY IN THE CONTEXT OF INTERRELIGIOUS DIALOGUE - Nihorowa, Precious (Asian Horizons, 2019)
In recent years, interreligious dialogue has been a burning topic among theologians across the religious divide. With the rise and influence of globalization and migration, the world is becoming more and more a global village and experiencing a growing need for interaction and unity. Efforts to attain such unity have been evident in all spheres and sectors of life resulting into formation of organizations and unions to facilitate the same. In the religious circles, there have also been similar efforts. The Second Vatican Council is a good example and perhaps a notable fountain of other efforts that the Church has made towards achieving fruitful dialogue with other religions. However, every time believers of different religions meet for a roundtable discussion to engage in dialogue, one of the apparent obstacles has been the claim to uniqueness and universality on the part of each of the parties. Thus, each of the parties has been setting forth the founders of their religions as a no-go zone for interreligious dialogue. This entails that the dialogue begins from such a claim as a condition. With the aid of some selected theologians and the encyclical Ecclesiam Suam and other Church documents, this article examines the concept of uniqueness and universality in interreligious dialogue. It argues that in as much as such a concept is viewed as an obstacle, there is a sense in which it can lay a good foundation for fruitful interreligious dialogue.